1995
DOI: 10.1016/0014-5793(95)00721-k
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus‐driven expression and purification of glycine receptor α1 homo‐oligomers

Abstract: The glycine receptor is a figand-gated anion channel protein of postsynaptic membranes. We expressed a homo-oligomeric receptor composed of human al subunits in Spodoptera frugiperda cells by infection with a recombinant Autographa californica nuclear polyhedrosis virus. A substantial fraction of the recombinant receptor was incorporated as a functional channel protein into the cell's plasma membrane at expression levels 4-to 30-fold higher than in other eukaryotic heterologous expression systems or native rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Homo-oligomers are often the active forms of many DNA replication-specific expression factors in baculovirus [ 18 , 19 ]. Previous studies have shown that oligomers of several genes, including lef-1 , lef-2 , ie-1 , ie-2 , lef-5 , dbp , ha44 and cg30 , are required for regulating DNA replication during AcMNPV proliferation [ 20 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homo-oligomers are often the active forms of many DNA replication-specific expression factors in baculovirus [ 18 , 19 ]. Previous studies have shown that oligomers of several genes, including lef-1 , lef-2 , ie-1 , ie-2 , lef-5 , dbp , ha44 and cg30 , are required for regulating DNA replication during AcMNPV proliferation [ 20 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After blocking in 10% (wt/vol) nonfat dry milk in PBS overnight at 4°C, the blot was incubated with hybridoma supernatants of the monoclonal Drosophila lamin Dm 0 antibodies U25 (undiluted; kindly provided by H. Saumweber, Humboldt University, Berlin, Germany; Risau et al, 1981 ) and ADL67 (dilution 1:20; kindly provided by N. Stuurman, Biozentrum, Basel, Switzerland; Riemer et al, 1995 ) or of the Drosophila lamin C antibody LC28 (dilution 1:20; also provided by N. Stuurmann; Riemer et al, 1995 ) for 2 h at room temperature. Subsequent incubation with alkaline phosphatase-conjugated anti–mouse antibodies ( Promega Biotech) and visualization with NBT/BCIP were performed as described ( Morr et al, 1995 ).…”
Section: Methodsmentioning
confidence: 99%